Predictors of Severe Acute Respiratory Syndrome Coronavirus 2 Infection Following High-Risk Exposure. (21st December 2021) - Andrejko, Kristin L; Pry, Jake; Myers, Jennifer F; Openshaw, John; Watt, James; Birkett, Nozomi; DeGuzman, Jennifer L; Barbaduomo, Camilla M; Dong, Zheng N; Fang, Anna T; Frost, Paulina M; Ho, Timothy; et al.
Abstract: Background: Non-pharmaceutical interventions (NPIs) are recommended for COVID-19 prevention. However, the effectiveness of NPIs in preventing SARS-CoV-2 transmission remains poorly quantified. Methods: We conducted a test-negative design case-control study enrolling cases (testing positive for SARS-CoV-2) and controls (testing negative) with molecular SARS-CoV-2 diagnostic test results reported to California Department of Public Health between 24 February–12 November, 2021. We used conditional logistic regression to estimate adjusted odds ratios (aORs) of case status among participants who reported contact with an individual known or suspected to have been infected with SARS-CoV-2 ("high-risk exposure") ≤14 days before testing. Results: 751 of 1448 cases (52%) and 255 of 1443 controls (18%) reported high-risk exposures ≤14 days before testing. Adjusted odds of case status were 3.02-fold (95% confidence interval: 1.75–5.22) higher when high-risk exposures occurred with household members (vs. other contacts), 2.10-fold (1.05–4.21) higher when exposures occurred indoors (vs. outdoors only), and 2.15-fold (1.27–3.67) higher when exposures lasted ≥3 hours (vs. shorter durations) among unvaccinated and partially-vaccinated individuals; excess risk associated with such exposures was mitigated among fully-vaccinated individuals. Cases were less likely than controls to report mask usage during high-risk exposures (aOR = 0.50 [0.29–0.85]). The adjusted odds of case status was lower for fully-vaccinated (aOR = 0.25 [0.15–0.43]) participants compared to unvaccinated participants. Benefits of mask usage were greatest among unvaccinated and partially-vaccinated participants, and in interactions involving non-household contacts or interactions occurring without physical contact. Conclusions: NPIs reduced the likelihood of SARS-CoV-2 infection following high-risk exposure. Vaccine effectiveness was substantial for partially and fully vaccinated persons. Abstract : SARS CoV-2 infection risk was greatest for unvaccinated participants when known or suspected exposures to cases occurred indoors or lasted ≥3 hours. Face mask usage when participants were exposed to a case reduced odds of infection by 50%.